Comparison of 2D and 3D Surface Roughness Parameters of AlMgSi0.5 Aluminium Alloy Surfaces Machined by Abrasive Waterjet - Csaba Felhő; Krisztina Kun-Bodnár; Zsolt Maros (Journal of Manufacturing and Materials Processing)
The use of 3D roughness parameters is increasingly gaining ground in various areas of engineering, especially in academic research. In many cases, however, these studies primarily cover the illustration of the character of the surfaces, the interpretation of areal numerical roughness values is often disputed. The goal of this paper is to examine how the 2D and 3D roughness parameters change in the case of anisotropic surfaces, such as surfaces cut with an abrasive water jet. For this purpose, abrasive water jet cutting experiments were performed on AlMgSi0.5 aluminum alloy using different technological parameters. After the experiments, two amplitude-type 3D roughness parameters (Sa and Sz) of the cut surface and four profile parameters (Ra, Rz for roughness and Pa, Pz for raw profile) were measured at five different depths. Our conducted research indicates that the 3D parameters represent a kind of average value for certain roughness characteristics and a maximum value for others. The paper also reports on how these roughness characteristics change as a function of feed speed.